2005
DOI: 10.1258/002221505774481273
|View full text |Cite
|
Sign up to set email alerts
|

Colonic carcinoma metastasis to the thyroid: a case of skip metastasis

Abstract: Colonic carcinoma metastasis to the thyroid is rare. Here the authors present the case of an 81-year-old lady who presented with metastatic colonic adenocarcinoma in her thyroid gland. This case is unique as it is the first to demonstrate metastasis from the colon to the thyroid with no other site involvement. The use of cytokeratin immunohistochemical staining is reviewed along with the current perspectives on the concept of skip metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…But metastases bypassing the liver have been mentioned in several reports over the years, involving the lungs and/or thyroid only. [3][4][5][6][7] The incidence of isolated lung without liver metastases in colon cancer patients ranged from 1% to 3.8% and was only mentioned in a few reports over the decades 3,4 compared to 5.9% in the present series.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…But metastases bypassing the liver have been mentioned in several reports over the years, involving the lungs and/or thyroid only. [3][4][5][6][7] The incidence of isolated lung without liver metastases in colon cancer patients ranged from 1% to 3.8% and was only mentioned in a few reports over the decades 3,4 compared to 5.9% in the present series.…”
Section: Discussionmentioning
confidence: 47%
“…But metastases bypassing the liver have been mentioned in several reports over the years, including to the lungs and thyroid. [3][4][5][6] Lung metastases are seen in about 10-15% of all colorectal cancer metastases, but only 10% of these are isolated in the absence of liver metastases. 3,4 The higher incidence of this isolated lung metastases in rectal compared to colonic carcinoma was attributed to the direct hematogenous spread into the systemic circulation via the inferior and middle rectal veins, bypassing the portal venous system.…”
Section: Introductionmentioning
confidence: 99%
“…have been reported [1][2][3][4] . Although metastases of these unusual sites from colorectal cancer might occur with the status of widespread disease, cardiac metastasis from colorectal cancer is extremely rare [5][6][7][8][9][10][11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…Unusual metastases from colorectal cancer into organs including the spleen, thyroid gland, spermatic cord, and skeletal muscle have been reported [1][2][3][4] . Although metastases to these sites might occur as a feature of end stagedisease, metastasis to the heart from colorectal cancer is extremely rare.…”
Section: Introductionmentioning
confidence: 99%
“…However, even then, without being informed of the possibility of metastasis, diagnosis of metastatic lesions to the thyroid can be rather confusing since the cytology features of metastatic high-grade malignancy are similar to rare primary thyroid malignancies such as anaplastic or clear cell thyroid carcinoma [3,4,6,35]. Additional immunohistochemical stains may also aid the diagnosis of metastasis, showing negative results for thyroglobulin and calcitonin and positive results for cytokeratin subtypes [12,27]. Four patients included in this study had undergone immunohistochemical staining of cytology specimens, all of which showed negative results for thyroglobulin.…”
Section: Discussionmentioning
confidence: 99%